Novel NiFe/NiFe-LDH composites as competitive catalysts for clean energy purposes - Sakita, A. M. P. [UNESP]; Valles, E.; Della Noce, R.; Benedetti, A. V. [UNESP] (Elsevier B.V., 2018)
The electrodeposition of metals generally employs several additives to avoid the formation of undesirable byproducts such as oxides and hydroxides. Although the deposition of metals is still the main goal in the most metals electroplating, the applicability of these byproducts might be an interesting field which is not explored in detail so far. In this work, the significance of water splitting reaction in clean energy production, employing NiFe hydroxides formed during the metals electrodeposition, is demonstrated for oxygen evolution reaction. The synthetized materials are composites of three components easily prepared in one-step by means of electrodeposition. Specifically, a granular NiFe alloy is obtained over which local pH variation and chloride presence induce the formation of a layered double hydroxide structure. The study of the influence of solution composition, deposition time, and deposition potential on the catalytic properties of the composites with respect to the oxygen evolution reaction are analyzed. Deposition times of few seconds, deposition potentials in the range -1.4 to -1.6 V vs. Ag/AgCl/KCl3M, and solutions containing Fe(II), Ni(II) and high chloride concentrations, lead to the best catalysts, showing an eta(10 mA cm 2) about 0.280 V. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Electrodeposition; Byproducts; Ni-Fe LDH; Oxygen evolution reaction